Transformasi Digital UMKM: Pengembangan Marketplace BANGKIT (Belanja UMKM Kreatif, Inovatif, dan Komplit) untuk Ekspansi Penjualan Produk Lokal UMKM Kabupaten Subang - Rahmat Irsyada; Lani Nurlani; Abd Rachman Mildan; Arnov Abdillah Rahman; Rachmad Augy; Nita Cahyani (Lembaga Pengembangan Kinerja Dosen, 2025)
Limitations in the adoption of digital technology are a major challenge for Micro, Small, and Medium Enterprises (MSMEs) in Subang Regency, which is reflected in the still-manual production process, conventional business management, and limited marketing reach on a local scale. On the other hand, the general public also faces low digital literacy which hinders participation in the modern economy. This community service program aims to address these problems through the design and development of an integrated marketplace platform called BANGKIT (Creative, Innovative, and Complete MSME Shopping). The program implementation method uses a participatory approach that includes three main stages: (1) development of the marketplace platform as a digital showcase for local products; (2) intensive training and mentoring for MSME actors regarding online store management, product photography, and digital marketing strategies; and (3) facilitation of the onboarding process for MSME products into the platform. The results of this activity are the realization of a functional digital economic ecosystem, increased capacity and empowerment of MSME partners, and expanded market reach for local products. This program not only provides concrete solutions for MSMEs, but also supports the achievement of the Key Performance Indicators (KPI) of higher education through the active involvement of lecturers and students in providing direct benefits to the community. Program outputs are disseminated through publications in community service journals, mass media, activity videos, poster works and reports on increasing the level of partner empowerment: management aspects.